Importance of serum calcium in spontaneous neck haematoma. Issue 9 (6th September 2020) - Zammit, Matthew; Siau, Richard; Panarese, Alessandro
Abstract : We present an unusual case of spontaneous cervical haemorrhage secondary to extra-capsular bleeding from a parathyroid adenoma. Signs and symptoms on presentation included sore throat, dysphagia and anterior chest ecchymosis. While CT confirmed active cervical haemorrhage, elevated serum calcium and parathyroid hormone raised suspicion of possible parathyroid pathology. This case report and literature review highlight the diagnostic value of serum calcium in presentations of acute spontaneous neck haematoma. This should be considered especially in the acute phase, where imaging may not identify the source of haemorrhage. Initial observation and deferred surgery is the treatment of choice, with emergency operative management reserved for respiratory distress and worsening compressive symptoms.